(untitled) (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2025)
In his scientific article, the author focuses on the variety of traditional Kyrgyz clothing in the epic “Manas”, which is the great heritage of the Kyrgyz people. Also, based on the information from the epic, the author attempted to interpret what the kyrgyz wore in everyday life and during the war. Since “Manas” is a heroic epic, it mainly describes the types of clothing of warriors. Ak olpok, charaina, chopkut and kandagai are especially mentioned as protective clothing that the hero wore when he went out on reconnaissance. They were so strong that it was impossible to pierce them with a spear or cut them with a sword. The article contains research work on the peculiarities of making types of clothing that reveal the full meaning of the kyrgyz people.